The Efficacy Of The Prefabricated T4FTM Myofunctional Appliance In Comparison To Twin Block Appliance For Class II Division 1 Malocclusion Treatment: A Randomized Clinical Trial - Hanoun, Abdulfatah Abdulrazak (2010)

(untitled)
Functional appliances are widely used to treat Class II Division 1 malocclusion. No previous studies were published about the effects of prefabricated re-mouldable functional appliance (T4FTM) for Class II Division 1 malocclusion on Class II skeletal pattern subjects. The aim of this study was to compare the changes in the skeletal and dentoalveolar structures in growing Malay patients (pre-adolescent) with Class II Division 1 malocclusion treated by Prefabricated Re-mouldable Myofunctional appliance T4FTM and Twin Block appliance (TB). A randomized clinical trial was carried out with a sample of 43 subjects (22 males + 21 females) randomly assigned to active control group (Twin Block group) and experimental group (T4FTM appliance group). At the end of six months study period and due to the drop out, TB group consisted of 17 subjects (8 males + 9 females), while T4FTM group consisted of 16 subjects (9 males + 7 females). Mean age was 13 years (0.7) in T4FTM group, and 13.2 years (0.8) in Twin Block group.